Biofabrication of a shape-stable auricular structure for the reconstruction of ear deformities. (January 2021) - Otto, I.A.; Capendale, P.E.; Garcia, J.P.; de Ruijter, M.; van Doremalen, R.F.M.; Castilho, M.; Lawson, T.; Grinstaff, M.W.; Breugem, C.C.; Kon, M.; Levato, R.; Malda, J.
Abstract: Bioengineering of the human auricle remains a significant challenge, where the complex and unique shape, the generation of high-quality neocartilage, and shape preservation are key factors. Future regenerative medicine–based approaches for auricular cartilage reconstruction will benefit from a smart combination of various strategies. Our approach to fabrication of an ear-shaped construct uses hybrid bioprinting techniques, a recently identified progenitor cell population, previously validated biomaterials, and a smart scaffold design. Specifically, we generated a 3D-printed polycaprolactone (PCL) scaffold via fused deposition modeling, photocrosslinked a human auricular cartilage progenitor cell–laden gelatin methacryloyl (gelMA) hydrogel within the scaffold, and cultured the bioengineered structure in vitro in chondrogenic media for 30 days. Our results show that the fabrication process maintains the viability and chondrogenic phenotype of the cells, that the compressive properties of the combined PCL and gelMA hybrid auricular constructs are similar to native auricular cartilage, and that biofabricated hybrid auricular structures exhibit excellent shape fidelity compared with the 3D digital model along with deposition of cartilage-like matrix in both peripheral and central areas of the auricular structure. Our strategy affords an anatomically enhanced auricular structure with appropriate mechanical properties, ensures adequate preservation of the auricular shape during a dynamic in vitro culture period, and enables chondrogenically potent progenitor cells to produce abundant cartilage-like matrix throughout the auricular construct. The combination of smart scaffold design with 3D bioprinting and cartilage progenitor cells holds promise for the development of clinically translatable regenerative medicine strategies for auricular reconstruction. Graphical abstract: Image 1 Highlights: First application of human auricular cartilage progenitor cells for bioprinting. Dual-printing of hybrid ear-shaped constructs with excellent shape fidelity over time. Strategy and design ensured adequate deposition of cartilage-like matrix throughout large auricular constructs.